Strong spatial structuring of clonal genetic diversity within blackthorn (Prunus spinosa) hedgerows and woodlands - James A. Brown; W. Ian Montgomery; Jim Provan (Tree Genetics & Genomes, 2022)
Hedgerows are an important component of agricultural landscapes, but in recent years have increasingly faced threats such as habitat loss, land use change, climate change, invasive species, pests and plant pathogens. Given the potential importance of genetic diversity in countering these threats, and the spatial distribution of such diversity within and across natural populations, we analyzed levels and patterns of diversity in blackthorn ( Prunus spinosa ), a key component of many hedgerows. Twenty-one populations of blackthorn from a mixture of hedgerows and woodlands were genotyped for four nuclear and five chloroplast microsatellites. Three hundred twenty-one unique clonal genotypes were identified from 558 individuals analyzed, 207 of which were found in a single individual. With the exception of a single population that appears to have been planted recently from seed (Peatlands Park), all populations exhibited evidence of vegetative reproduction via suckering. Multi-ramet clones were highly spatially structured within populations, and ranged in size from < 1 to 258 m. These findings indicate that asexual reproduction is widespread in the populations of blackthorn studied. Although levels of clonality varied across study sites, there was clear spatial structuring of clones in each case. Such clonal organization should be taken into account in hedge management or where planting or replanting of hedgerows becomes necessary. Knowledge of the patterns and extent of spatial structuring of genotypes within potential source populations will allow the selection of genetically divergent material, rather than selection of clonal replicates of the same genotype.

Broad-scale genetic homogeneity in natural populations of common hazel (Corylus avellana) in Ireland - James A. Brown; Gemma E. Beatty; W. Ian Montgomery; Jim Provan (Tree Genetics & Genomes, 2016)

Genetic analyses reveal high levels of seed and pollen flow in hawthorn (Crataegus monogyna Jacq.), a key component of hedgerows - James A. Brown; Gemma E. Beatty; Caroline M. V. Finlay; W. Ian Montgomery; David G. Tosh; Jim Provan (Tree Genetics & Genomes, 2016)

Genetic provenance and best practice woodland management: a case study in native alder (Alnus glutinosa) - Gemma E. Beatty; W. Ian Montgomery; David G. Tosh; Jim Provan (Tree Genetics & Genomes, 2015)

Lack of genetic structure and evidence for long-distance dispersal in ash (Fraxinus excelsior) populations under threat from an emergent fungal pathogen: implications for restorative planting - Gemma E. Beatty; James A. Brown; Eamon M. Cassidy; Caroline M. V. Finlay; Lorraine McKendrick; W. Ian Montgomery; Neil Reid; David G. Tosh; Jim Provan (Tree Genetics & Genomes, 2015)